A phylogenomic analysis of Marek's disease virus reveals independent paths to virulence in Eurasia and North America. (3rd September 2017) - Trimpert, Jakob; Groenke, Nicole; Jenckel, Maria; He, Shulin; Kunec, Dusan; Szpara, Moriah L.; Spatz, Stephen J.; Osterrieder, Nikolaus; McMahon, Dino P.
Abstract: Virulence determines the impact a pathogen has on the fitness of its host, yet current understanding of the evolutionary origins and causes of virulence of many pathogens is surprisingly incomplete. Here, we explore the evolution of Marek's disease virus (MDV), a herpesvirus commonly afflicting chickens and rarely other avian species. The history of MDV in the 20th century represents an important case study in the evolution of virulence. The severity of MDV infection in chickens has been rising steadily since the adoption of intensive farming techniques and vaccination programs in the 1950s and 1970s, respectively. It has remained uncertain, however, which of these factors is causally more responsible for the observed increase in virulence of circulating viruses. We conducted a phylogenomic study to understand the evolution of MDV in the context of dramatic changes to poultry farming and disease control. Our analysis reveals evidence of geographical structuring of MDV strains, with reconstructions supporting the emergence of virulent viruses independently in North America and Eurasia. Of note, the emergence of virulent viruses appears to coincide approximately with the introduction of comprehensive vaccination on both continents. The time‐dated phylogeny also indicated that MDV has a mean evolutionary rate of ~1.6 × 10 −5 substitutions per site per year. An examination of gene‐linked mutations did not identify a strong association between mutational variation and virulence phenotypes, indicating that MDV may evolve readily and rapidly under strong selective pressures and that multiple genotypic pathways may underlie virulence adaptation in MDV.